Base Nacional Comum Curricular do Ensino Médio: uma análise crítica do eixo da prática de análise linguística/semiótica - Padoin, Verônica Lorenset (2023)
This research aims to investigate how the Linguistic Analysis Practice is contemplated in skills in the National Common Curricular Base (BNCC) of High School, considering the context in which the document was produced and the pedagogical foundations of Portuguese language curriculum component. The general objective unfolds into the following specific objectives: i) identify and analyze the pedagogical foundations that guide the high school stage and the Portuguese language curricular component; ii) analyze Portuguese language skills considering the nature of the processes (cognitive processes), the nature of the participants (objects of knowledge) and the circumstances (learning context) in light of the transitivity system of Systemic-Functional Grammar. The theoreticalmethodological contribution consists of a historical rescue of High School in Brazil, from the first secondary education establishment to the latest changes provided for by Law nº 13.415/2017 and materialized by the National Common Curricular Base of High School, in addition to a brief overview of Portuguese language teaching in Brazil (SOARES, 2004), which includes the emergence and establishment of the concept of Linguistic Analysis Practice (GERALDI, 1997; 2011 [1984]; FRANCHI, 1992 [1987]) and its main concepts, and the basic aspects of Systemic-Functional Linguistics (HALLIDAY; MATTHIESSEN, 2014), chosen as the analysis theory. The corpus is constituted by the National Common Curricular Base of High School, specifically by the sections dedicated to the area of Languages and its technologies and to the Portuguese language curricular component and to the linguistic/semiotic analysis skills of this component. The results of the analysis indicate that the BNCC was a document constructed in the face of a troubled historical period, marked by political tension, which had a direct impact on its structure and organization, thus demonstrating the direct relationship between the context of production and the text. Regarding the foundations that guide the High School stage, it was possible to identify five dimensions: i) youth and youth cultures; ii) life project; iii) curriculum flexibility; iv) new digital technologies; and v) world of work and development of critical thinking. These dimensions are also mobilized in the Portuguese language curricular component based on the relationship with linguistic phenomena. In this case, the dimensions of youth and youth cultures, new digital technologies and the development of critical thinking stand out. The High School BNCC proposes 54 skills, of which 11 mobilize objects of knowledge from the practice of language linguistic/semiotic analysis, which made up the corpus of analysis. From the investigation carried out, we could realize that the identified skills mobilize the Linguistic Analysis Practice, considering that they recover the characteristic theoretical-methodological aspects of Linguistic Analysis Practice. Despite this, it should be noted that these skills are not distributed across all fields of activity, and there is a certain imbalance in the mobilization of language practices, given that skills involving PAL are a minority in relation to other teaching axes. Furthermore, a significant portion of the analyzed skills deviate from the typical structure presented by the Base, which may impair the recontextualization of language practices in the classroom.